Factors affecting early grade educational attainment: Evidence from South Sudan - Raza, Wameq A; Kabir, Md Mahbubul; Rashid, Rafiath (Science Direct, 2022)
This article was published in The International Journal of Educational Development [© 2017 Elsevier Ltd. All rights reserved.] and the definite version is available at: https://doi.org/10.1016/j.ijedudev.2017.08.004 The Article's website is at: https://www.sciencedirect.com/science/article/abs/pii/S0738059316303911?via%3Dihub#!